EVALUASI POLA OPERASI WADUK GAJAH MUNGKUR DENGAN ADANYA SPAM REGIONAL WOSUSOKAS - Koes Paulina Cantik, Bella; Dharsono, Mulyadi Sugih; Nur Afifah, Kisindi; Stephanie, Kezya (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2024)
Gajah Mungkur reservoir is one of the largest multipurpose reservoirs in Java with 100 years of useful life. The purpose of the Gajah Mungkur Reservoir is not only as a flood control, but also for other needs such as hydropower, irrigation and raw water. The construction of the Wosusokas is to objectify the purpose of the reservoir for the distribution of raw water to several regions, namely Gajah Mungkur, Sukoharjo, Solo, and Karanganyar. The purpose of this study was to determine the reliability of the reservoir’s use for raw water with the Wosusokas transmission pipeline network. The method is to simulate a simple operating pattern at the Gajah Mungkur Reservoir using the Standard Operating Rule (SOR) with the target release for irrigation water and raw water. The research findings indicate that more than 70% of the actual release for meeting the needs of irrigation and fulfilling raw water supply is the value of the target release for meeting the needs of irrigation and fulfilling raw water supply. The calculation results also show the percentage of reliability for raw water in 2017 was 100%, while the percentage of reliability in 2018 was 45,833%, and the percentage of reliability from January 2019 to July 2019 was 76,923%.